2016
DOI: 10.1121/1.4941451
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-spreading harmonic complex as an alternative carrier for vocoder simulations of cochlear implants

Abstract: Noise- and sine-carrier vocoders are often used to acoustically simulate the information transmitted by a cochlear implant (CI). However, sine-waves fail to mimic the broad spread of excitation produced by a CI and noise-bands contain intrinsic modulations that are absent in CIs. The present study proposes pulse-spreading harmonic complexes (PSHCs) as an alternative acoustic carrier in vocoders. Sentence-in-noise recognition was measured in 12 normal-hearing subjects for noise-, sine-, and PSHC-vocoders. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The PSHC carriers all had a fundamental frequency of 0.3 Hz. The PSHC pulse rate differed across bands and was a function of the center frequency of the corresponding synthesis bandpass filter following the equation in Figure 1 of Mesnildrey et al. (2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSHC carriers all had a fundamental frequency of 0.3 Hz. The PSHC pulse rate differed across bands and was a function of the center frequency of the corresponding synthesis bandpass filter following the equation in Figure 1 of Mesnildrey et al. (2016).…”
Section: Methodsmentioning
confidence: 99%
“…This equation provides the pulse rate yielding a minimum of intrinsic modulations after auditory filtering, given the center frequency of the synthesis filter. Similar to Mesnildrey et al. (2016), the cutoff frequency of the envelope extraction stage was equal to half the PSHC pulse rate in cases where it was lower than 200 Hz but was otherwise limited to 200 Hz to mimic the poor salience of temporal pitch cues experienced by CI listeners at high rates (e.g., Kong & Carlyon, 2010; Townshend, Cotter, Van Compernolle, & White, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that the listeners in the CI simulation experiment showed a greater MPB than the CI users despite the use of a noise-excited vocoder simulation. The inherent random modulations of a noise carrier are known to make it more difficult to detect a target modulation (Dau et al, 1997) and in line with this, CI simulations using tone-vocoders (Whitmal III et al, 2007) and pulse-spreading harmonic complexes (Mesnildrey et al, 2016) have reported better speech perception in the presence of a masker. Accordingly, using these types of carriers would likely resulted in an even larger MPB.…”
Section: B Masker-periodicity Benefitmentioning
confidence: 80%
“…Simulations with less than eight channels presented to normal-hearing listeners provide speech intelligibility scores in the same range as CI patients [1], [2]. Despite this good result, some researchers argue that the vocoded information does not offer the same sound quality as that of CIs and suggest the existence of perceptual and informational discrepancies between CI stimulation and performance-matched acoustical simulations [3][4][5][6]. Thus, a similar level of performance obtained for both real and simulated CI may hide different patterns of errors, limiting the validity of acoustic simulations through vocoders to evaluate new coding strategies.…”
Section: Introductionmentioning
confidence: 99%